1987
DOI: 10.1017/s0014479700001174
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Elemental Sulphur on Shoot Dry Weight, Nodulation and Pod Yield of Groundnut (Arachis hypogaea) under Irrigation

Abstract: SUMMARYField experiments were carried out to study the effects of elemental sulphur on irrigated groundnut. The sulphur was applied at rates of 50, 100 or 150 kg ha−1, either at sowing, at flowering or in two equal splits at sowing and flowering. Shoot dry weight, total sulphur content of leaves, nodule number per plant and pod yield were all significantly increased by sulphur treatment, but nodule dry weight was unaffected. The greatest response lay at or below 50 kg ha−1 applied at sowing. There were no furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…O'Hara et al (1988) observed that Fe-deficient groundnut grown on cal- (Singh and Chaudhari, 1995). However, Hago and Salama (1987) found that application of elemental S at 50kg S ha"' increased the nodule number per plant but not the nodule dry weight. Though in our earlier study iron sulfate was found to be best (Singh et al, 1990), the chloride salts of Fe, Mn, and Zn were used in this study to differentiate the effects of sulphur from micronutrients and the individual effects of these micronutrients were found promising.…”
Section: Growth Nodulation Dry Matter Production and Yieldsmentioning
confidence: 88%
See 2 more Smart Citations
“…O'Hara et al (1988) observed that Fe-deficient groundnut grown on cal- (Singh and Chaudhari, 1995). However, Hago and Salama (1987) found that application of elemental S at 50kg S ha"' increased the nodule number per plant but not the nodule dry weight. Though in our earlier study iron sulfate was found to be best (Singh et al, 1990), the chloride salts of Fe, Mn, and Zn were used in this study to differentiate the effects of sulphur from micronutrients and the individual effects of these micronutrients were found promising.…”
Section: Growth Nodulation Dry Matter Production and Yieldsmentioning
confidence: 88%
“…When grown on a calcareous soil, the groundnut shows chlorosis mainly due to the lime-induced deficiencies of sulphur and micronutrients such as Fe, Zn, and Mn causing considerable yield reductions (Hartzook, 1975;Houng, 1984;Singh and Dayal, 1992;Singh etal., 1990Singh etal., ,1993Singh etal., ,1995Singh and Chaudhari, 1995). In groundnut, these deficiencies occur mainly in young and developing leaves as interveinal to complete leaf blade chlorosis which sometimes may turn pale yellow or white causing death of leaflets and plants (Hartzook, 1975;Hago and Salama, 1987;Dwivedi, 1988;Supakamnerd et al, 1990;Singh et al, 1990Singh et al, , 1995Singh and Chaudhari, 1995). These deficiencies are so intermingled that it is very difficult to single them out in field-grown crops, especially in calcareous soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of sulfur and/or inoculation of the thiosulfate-oxidizing bacteria enhanced the shoot and root length and the plant biomass of the maize. Several earlier reports have also noted the beneficial effect of sulfur application for the crop growth of groundnut, canola and maize (Hago and Salama, 1987;Blake-Kalff et al, 1998;Histuda et al, 2005;El-Tarabily et al, 2006). Deficiency symptom was also observed with the control treatments, where all the nutrients, except for sulfur, were amended, thereby implying that the application of NPK alone is not sufficient for overall plant growth.…”
Section: Discussionmentioning
confidence: 86%